2019
DOI: 10.3390/md17120677
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multitrophic Aquaculture By-Products with Added Value: The Polychaete Sabella spallanzanii and the Seaweed Chaetomorpha linum as Potential Dietary Ingredients

Abstract: Aquaculture expansion is limited by the negative environmental impact of the waste and the need for alternative sources in the diet of reared fish. In this framework, for the first time, the survival rates, biomass gain, and fatty acid profiles of the polychaete Sabella spallanzanii and the macroalga Chaetomorpha linum, reared/cultivated as bioremediators in an integrated multitrophic aquaculture system (IMTA), were evaluated for their potential reuse applications. Results showed that these organisms represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
2
21
1
Order By: Relevance
“…The co‐occurrence of these filter feeders furnishes relevant ecosystem services, in that they effectually clear particulate organic matter and also pseudofeces produced by mussels, which are cultured intensively in the area, acting as bioremediators (Giangrande, Pierri, et al, 2014). Moreover, sabellids are promising even from an economic point of view; owing to their conspicuous and attractive features, their biomass could be employed in aquaculture food production (Stabili et al, 2019) or as ornamental invertebrates for aquariums in order to reduce the unsustainable trade of species imported from tropical areas (Murray, Watson, Giangrande, Licciano, & Bentley, 2013). This is an interesting and relevant case study that shows the potential positive ecological (bioremediation) and economic impact of some AS, as already proposed by Fanelli (2016), and calls for European regulations in this regard, as, at the moment, the use of AS is not permitted by current European regulations.…”
Section: The Other Side Of Biological Invasionsmentioning
confidence: 99%
“…The co‐occurrence of these filter feeders furnishes relevant ecosystem services, in that they effectually clear particulate organic matter and also pseudofeces produced by mussels, which are cultured intensively in the area, acting as bioremediators (Giangrande, Pierri, et al, 2014). Moreover, sabellids are promising even from an economic point of view; owing to their conspicuous and attractive features, their biomass could be employed in aquaculture food production (Stabili et al, 2019) or as ornamental invertebrates for aquariums in order to reduce the unsustainable trade of species imported from tropical areas (Murray, Watson, Giangrande, Licciano, & Bentley, 2013). This is an interesting and relevant case study that shows the potential positive ecological (bioremediation) and economic impact of some AS, as already proposed by Fanelli (2016), and calls for European regulations in this regard, as, at the moment, the use of AS is not permitted by current European regulations.…”
Section: The Other Side Of Biological Invasionsmentioning
confidence: 99%
“…Observed peaks were attributed to the tetrapyrrole ring N–H protons signals 17 . In particular, signals at 11.16, 11.18, 10.47, 10.37, and in the range 9.95–9.6 ppm were assigned to chlorophyll b, while chlorophyll a and its pheophytins derivatives resonances were observed in the range 9.6–9.32 ppm and 8.53–8.1 ppm 26 , 27 .…”
Section: Resultsmentioning
confidence: 97%
“…All the 1 H-NMR spectra were calibrated to the internal standard TMS (δ = 0.00 ppm). Characterization of metabolites was performed by the analysis of two-dimensional homo- and heteronuclear NMR spectra (2D 1 H J-resolved, 1 H COSY, 1 H- 13 C HSQC, and HMBC) and by comparison with published data 17 , 21 , 22 , 24 27 , 58 .…”
Section: Methodsmentioning
confidence: 99%
“…This species was chosen because it represents a natural and abundant element of the fouling communities all around in the area [73][74][75]77]. Of the 196 collectors, only 184 were followed until the end of the year cycle because some of them were utilized for a previous experimentation on S. spallanzanii biomass [78].…”
Section: Field Work: Sampling and Processingmentioning
confidence: 99%
“…Macroalgae could be an important by product too, highlighting their capacity of producing bioactive compounds for multiple applications [49,78,[112][113][114]. In particular, in the lipidic extract of C. linum from the Taranto sea, Stabili et al [49] demonstrated the existence of antibacterial and antioxidant activity against common pathogens in aquaculture, such as Vibrio ordalii and Vibrio vulnificus.…”
Section: Conclusive Remarksmentioning
confidence: 99%